Analysis of cofermentation characteristics of Lactobacillus bulgaricus and Streptococcus thermophilus based on microrheology. Issue 3 (2nd December 2022) - Yang, Shujuan; Li, Weicheng; Bai, Mei; Wang, Jicheng; Sun, Zhihong
Abstract: The fermented milk mainly consists of Lactobacillus bulgaricus and Streptococcus thermophilus . This research was aimed to investigate the cofermentation characteristics of different L. bulgaricus and S. thermophilus strains. Three strains of L. bulgaricus and S. thermophilus ST‐2 were mixed and prepared into the starter (A, B, and C) and applied to milk fermentation for screening of optimal combination, and the commercial starter (D) was used as the reference. The microrheological properties during fermentation were analyzed by using multifrequency diffusion spectroscopy. Meanwhile, the fermented milk's stability, texture, and sensory characteristics were also observed during storage. Microrheology analysis revealed that the time to reach the fermentation endpoint of starters A, B, and C was almost the same during fermentation. Groups A, B, and C showed more elastic solid‐state properties and groups A and C had higher elastic factors, indicating that the gel structure of the sample was relatively strong. During storage, the pH value of fermented milk in each group D, A, C, and B was in sequence from high to low, and the titratable acidity was also in sequence from high to low in B, C, A, and D groups, respectively. The viscosity of group A was significantly higher than that of groups B and C ( p < 0.05), and there was no change in group D ( p > 0.05). The sensory score of fermented milk in group A was higher, and the overall texture was good. Results concluded that group A starter culture produced fermented milk with a firm gel structure and excellent texture and flavor. This study will provide data support and methodology for developing and screening compound starters applied for milk fermentation in the future. Abstract : The microrheological properties of different starter combinations ( Lactobacillus bulgaricus and Streptococcus thermophilus ) in the milk fermentation process were analyzed by multifrequency diffusion spectroscopy. Meanwhile, the fermented milk's stability, texture, and sensory characteristics were also observed during storage. This study will provide data support and methodology for developing and screening compound starters applied for milk fermentation in the future.